2019
DOI: 10.11604/pamj.2019.32.74.18076
|View full text |Cite
|
Sign up to set email alerts
|

Ostéochondrome solitaire de la symphyse pubienne de découverte fortuite

Abstract: L'ostéochondrome est la tumeur osseuse bénigne la plus fréquente. Elle touche habituellement les métaphyses des os longs, particulièrement autour du genou et de l'humérus proximal. Il touche très rarement la symphyse pubienne avec fréquemment une symptomatologie atypique. Nous rapportons le cas d'un ostéochondrome de la symphyse pubienne empiétant sur la branche osseuse ilio-pubienne chez un homme de 35 ans, de découverte fortuite. Les explorations radiologiques, l'examen macroscopique et histologique confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…We performed an extensive review of available reports about osteochondroma near the pubic symphysis from 1980 to the present (Table 1 ). Amis [ 7 ], Cardenas [ 12 ] and Bacha [ 13 ] described asymptomatic patients at the time of routine physical examination. Phillips [ 4 ] reported that exostosis arising from the superior aspect of the right pubic ramus had a close relationship with the prostate and bladder base.…”
Section: Discussionmentioning
confidence: 99%
“…We performed an extensive review of available reports about osteochondroma near the pubic symphysis from 1980 to the present (Table 1 ). Amis [ 7 ], Cardenas [ 12 ] and Bacha [ 13 ] described asymptomatic patients at the time of routine physical examination. Phillips [ 4 ] reported that exostosis arising from the superior aspect of the right pubic ramus had a close relationship with the prostate and bladder base.…”
Section: Discussionmentioning
confidence: 99%